Antioxidant and antiproliferative potential of biosurfactants isolated from Lactobacillus casei and their anti-biofilm effect in oral Staphylococcus aureus strains. (March 2017) - Merghni, Abderrahmen; Dallel, Ines; Noumi, Emira; Kadmi, Yassine; Hentati, Hajer; Tobji, Samir; Ben Amor, Adel; Mastouri, Maha
Abstract: Biosurfactants also called bioemulsifiers are amphipathic compounds produced by many microorganisms that allow them to exhibit a wide range of biological activities. The aim of this study was to determine the antioxidant and antiproliferative potential of biosurfactants isolated from Lactobacillus casei and to assess their anti-adhesive and anti-biofilm abilities against oral opportunistic Staphylococcus aureus strains. The antioxidant activity of biosurfactant was evaluated using the in vitro scavenging ability on 1, 1-diphenyl-2-picrylhydrazyl (DPPH) radical. The antiproliferative activity was determined on epithelial cell line (HEp-2) by the Methylthiazole tetrazolium (MTT) reduction assay. The anti-adhesive and antibiofilm activity against S. aureus strains were achieved using crystal violet staining. Our results revealed that the DPPH scavenging activity of biosurfactants at 5.0 mg/mL concentration is between 74.6 and 77.3%. Furthermore, biosurfactants showed antiproliferative potency against studied epithelial cells as judged by IC50 and its value ranged from 109.1 ± 0.84 mg/mL to 129.7 ± 0.52 mg/mL. The results of the growth inhibition indicate that biosurfactant BS-LBl was more effective against oral S. aureus strains 9P and 29P with an IC50 of 1.92 ± 0.26 mg/mL and 2.16 ± 0.12 mg/mL respectively. Moreover, both biosurfactants displayed important antibiofilm activity with eradication percentages ranging from 80.22 ± 1.33% to 86.21 ± 2.94% for the BS-LBl, and from 53.38 ± 1.77% to 64.42 ± 2.09% for the BS-LZ9. Our findings demonstrate that biosurfactants from L. casei strains exhibited considerable antioxidant and antiproliferative potencies and were able to inhibit oral S. aureus strains with important antibiofilm efficacy. They could have a promising role in the prevention of oral diseases. Highlights: Biological activities of biosurfactants BS-Bl and BS-Z9 derived from Lactobacillus casei were tested. Biosurfactants exhibited antioxidant activity and antiproliferative property on epithelial cells. Biosurfactants showed a prominent antibiofilm effect against oral Staphylococcus aureus strains.